Spain : Financial Sector Assessment Program-Technical Note-Insolvency and Creditor Rights. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Note discusses the findings and recommendations in the Financial Sector Assessment Program for Spain in the areas of insolvency and creditor rights. The regime for creditor and debtor rights largely conforms to international best practices. With respect to creditor and debtor rights, the registration of real estate mortgages is efficient, reliable, and cost-effective. Owing to nonperforming loans, real estate foreclosure has been extensively used in Spain. Real estate collateral plays a critical role in Spain owing to the fact that a very large percentage of loans are collateralized with real estate. The institutional framework supporting insolvency and creditor rights has been strengthened but requires further reinforcement and more resources.